A method for preparing polyurethane hot melt adhesive for wood edge banding
By adding specific ingredients to the polyurethane hot melt adhesive and performing special treatment, the problems of slow curing speed, poor adhesive performance and harmful gas release in wood edge sealing applications are solved, and the effects of high curing speed, excellent adhesive performance and low harmful gas release are achieved.
Patent Information
- Application Number
- CN202510036503.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane hot melt adhesives are slow to cure and have poor adhesive properties in wood edge sealing applications, and may release harmful gases, affecting environmental protection and health.
A high-performance polyurethane hot melt adhesive was prepared by mixing isocyanate and plant-based polyol, and adding catalyst, polypropylene carbonate, nanocomposite microcapsules, modified nanomineral crystals, modified mineral wool and tackifier. The mixture was carried out in stirring reactions and high-temperature mixing.
It significantly improves the curing speed and adhesion performance of polyurethane hot melt adhesive, reduces the release of harmful gases, enhances the aging resistance of the glue layer, and is suitable for maintaining excellent adhesion performance in environments with large temperature changes.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing polyurethane hot melt adhesive for wood edge banding, belonging to the technical field of hot melt adhesives. Background Art
[0002] In the wood industry, edge banding is an important process, which mainly involves sealing the edge of the board by gluing and pressing the edge banding strips. The edge-banded board has good durability and aesthetics and is often used in the preparation of home furnishing materials. At present, environmentally friendly home furnishing materials are gradually gaining attention in the market, and environmental protection and health have become important considerations for consumers when purchasing home furnishing products. However, harmful gases such as formaldehyde may exist or be released inside the board and in the edge banding glue, which will limit the market for edge-banded boards.
[0003] Polyurethane hot melt adhesive is usually used for wood edge banding because of its advantages such as high bonding strength and good stability. However, polyurethane hot melt adhesive also has some disadvantages, such as slow curing speed, poor heat resistance, and harmful gas release during use. In particular, wood is a hygroscopic material, and its moisture content will change due to the influence of external temperature and humidity, which will affect the bonding performance of polyurethane hot melt adhesive. Therefore, the development of a polyurethane hot melt adhesive suitable for wood edge banding, which not only has a fast curing speed and good bonding performance, but also can reduce the release of harmful gases, has become a current research hotspot. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a polyurethane hot melt adhesive for wood edge banding, which can accelerate the curing speed of the polyurethane hot melt adhesive, improve the bonding performance of the polyurethane hot melt adhesive, and reduce the harmful gases generated by the polyurethane hot melt adhesive.
[0005] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows: A method for preparing a polyurethane hot melt adhesive for wood edge banding comprises the following steps: (1) Mix isocyanate and polyol, add catalyst, and stir to react at 70-85°C for 20-30 minutes; (2) Add polypropylene carbonate, nanocomposite microcapsules, modified nano mineral crystals, modified mineral wool, and a tackifier to the solution of step (1), and mix at 100-130° C. for 2-3 hours to obtain a polyurethane hot melt adhesive.
[0006] Furthermore, the components of the polyurethane hot melt adhesive are: by weight, 40-60 parts of isocyanate, 50-70 parts of polyol, 0.5-2.0 parts of catalyst, 10-15 parts of polypropylene carbonate, 10-15 parts of nanocomposite microcapsules, 3-5 parts of modified nano mineral crystals, 5-8 parts of modified mineral wool, and 10-20 parts of tackifier.
[0007] Furthermore, in step (1), the polyol is a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of (2-3):1. Polyol is one of the main raw materials of polyurethane hot melt adhesive. Since isocyanate can cause harm to the human body, non-toxic and harmless biomass polyol is selected to react with it to reduce the emission of harmful substances, which is more friendly to the environment and the human body. In addition, the selected raw materials are renewable biomass raw materials, which conforms to the concept of sustainable development. The polyurethane hot melt adhesive prepared by mixing plant-based polyol and vegetable oil-based polyol has excellent performance. Plant-based polyol contains a variety of active groups, which can improve the thermal stability and mechanical properties of the hot melt adhesive; vegetable oil-based polyol can increase the crosslinking degree and flexibility of the hot melt adhesive, improve its physical properties, and enhance its water resistance.
[0008] Furthermore, the preparation method of the plant-based polyol is: adding waste sawdust to a mixed solution of propylene glycol and glycerol, adding phosphoric acid, and heating to 135-155°C by microwave for 15-20 minutes; the preparation method of the vegetable oil-based polyol is: adding hydrogen peroxide and sulfuric acid to the vegetable oil, heating to 50-80°C for 4-10 hours, then adding ammonium bromide, heating to 90-130°C for 1-3 hours, adjusting the pH to 7-8, and distilling under reduced pressure. The hydroxyl groups in the polyol can form hydrogen bonds with the hydroxyl groups of the wood to enhance the bonding performance, and may also react with other groups in the wood under the action of the residual catalyst to further enhance the interaction between the two.
[0009] Furthermore, the mass ratio of propylene glycol to glycerol is 6:4, the mass ratio of waste sawdust to mixed solution is 1:(8-10), the amount of phosphoric acid added is 3-5% of the mass of the mixed solution, and the microwave power is 500-600w; the mass ratio of vegetable oil, hydrogen peroxide, sulfuric acid and ammonium bromide is 1:(0.4-0.7):(0.02-0.04):(0.03-0.08). During the production of boards, a large amount of waste sawdust will be generated. The liquefaction of the waste sawdust to prepare plant-based polyols is simple and convenient to operate, which can achieve the recycling of waste and reduce production costs.
[0010] Furthermore, in step (1), the stirring speed is 120-150 r / min.
[0011] Furthermore, in step (1), the catalyst is one of dimorpholine diethyl ether, triethylamine, dimethylethanolamine or N,N-dimethylcyclohexylamine; and the isocyanate is one of diisocyanate or triisocyanate.
[0012] Furthermore, in step (2), the preparation method of the polypropylene carbonate is: reacting carbon dioxide, propylene oxide and a catalyst at 80-120°C for 3-5h to obtain polypropylene carbonate. Carbon dioxide is produced by the reaction of isocyanate and plant-based polyols. The use of carbon dioxide to prepare polypropylene carbonate can reduce the generation of waste, prepare high value-added chemical products, and reduce greenhouse gas emissions, which is in line with the concept of green environmental protection. Polypropylene carbonate can react with isocyanate to synthesize a polyurethane hot melt adhesive with excellent chemical resistance and good low temperature resistance. When mixed with a polyurethane hot melt adhesive synthesized using plant-based polyols, the resulting polyurethane hot melt adhesive has excellent performance and outstanding bonding properties to wood.
[0013] Furthermore, the mass ratio of propylene oxide to catalyst is 1:(0.05-0.07); the catalyst is a mixture of alkali metal salt catalyst and organic amine catalyst in a mass ratio of 1:(0.8-1.1); and the reaction pressure is 0.1-10.0 MPa.
[0014] Furthermore, in step (2), the preparation method of the nanocomposite microcapsules is: (1) Adding negative ion mud, bentonite and nano-alumina to polyethylene glycol and hydrochloric acid solution, ultrasonicating for 30-40 minutes, then adding ammonia solution, heating to 90-110°C for reaction for 2-3 hours, filtering, drying and calcining for 3-5 hours to obtain a nano-alumina / negative ion mud-bentonite composite; (2) immersing the nano-alumina / negative ion mud-bentonite composite in a rare earth element salt solution, ultrasonicating for 20-30 minutes, filtering, washing, and drying at 100-120° C. to obtain a nano-composite loaded with rare earth elements; (3) Melamine and formaldehyde are reacted under alkaline conditions to form a prepolymer, and then the nanocomposite loaded with rare earth elements is emulsified at 25-30°C to form an emulsion. Finally, the prepolymer is adjusted to a pH of 5.0-5.5 with an acrylic acid solution, mixed with the emulsion for 15-20 minutes, filtered, and dried to obtain nanocomposite microcapsules.
[0015] Since wood is hygroscopic, its high moisture content will cause the bonding strength of hot melt adhesive to decrease. The present invention adds nanocomposite carrier microcapsules. During the process of squeezing and pressing, the microcapsule wall material breaks, and the nanocomposite loaded with rare earth elements can absorb the excess moisture released from the wood and accelerate the curing. Since the internal polyurethane hot melt adhesive cannot be exposed to moisture in the air, the curing speed is slow, and the negative ion mud can release moisture and accelerate the curing of the internal polyurethane hot melt adhesive. In addition, due to the long service life, the hot melt adhesive layer will age, resulting in the reduction of the bonding force of the hot melt adhesive layer and the phenomenon of warping of the edge sealing. The addition of nanocomposite microcapsules can effectively improve the aging resistance of the hot melt adhesive and extend the service life of the adhesive layer after bonding.
[0016] Furthermore, in step (1), the mass ratio of the negative ion mud, bentonite and nano-alumina is (1-1.5):1:(1.5-2.5).
[0017] Negative ion mud has strong moisture absorption and release functions. It can absorb moisture when the humidity is high and release moisture when the humidity is low, effectively regulating the dryness and wetness. It can also release a large amount of negative oxygen ions, which can decompose harmful substances such as formaldehyde. It also has extremely strong crack resistance and fire retardant properties.
[0018] Diatomaceous earth is a natural porous mineral with a very high specific surface area and adsorption capacity. It can absorb impurities on the surface of the board to prevent the impurities on the surface of the board from affecting the fit and flatness of the edge banding, thereby solving the problem of board edge warping due to poor bonding effect. In addition, diatomaceous earth can effectively remove odors from polyurethane hot melt adhesives and wood. Both negative ion mud and diatomaceous earth can improve the viscosity and mechanical properties of hot melt adhesives.
[0019] Alumina can improve the water resistance and thermal insulation performance of hot melt adhesive, and also improve the anti-aging performance of hot melt adhesive.
[0020] Rare earth elements can absorb ultraviolet rays, reduce the penetration and damage of ultraviolet rays, improve the anti-ultraviolet performance of hot melt adhesives, and delay the aging process of hot melt adhesives.
[0021] Furthermore, in step (1), the concentrations of the hydrochloric acid solution and the ammonia water are both 0.1 mol / L, and the volume ratio of the hydrochloric acid solution to the ammonia water is 1:(1-1.2); and the calcination temperature is 300-400°C.
[0022] Furthermore, in step (3), the molar ratio of melamine to formaldehyde is 1:(2-2.7); the concentration of the acrylic acid solution is 8.5-9.5wt.%. At this time, the wall material has moderate strength, and the wall material breaks after being pressed, and the nanocomposite loaded with rare earth elements is exposed. If the concentration of acrylic acid is high and the amount added when adjusting the pH is small, the system cannot polymerize into a strong pressure-resistant wall material, and it is easy to break in the subsequent preparation of silicone sealant; while if the concentration of acrylic acid is low and the amount added when adjusting the pH is large, the system polymerizes into a strong pressure-resistant wall material, and the wall material is not easy to break in the subsequent process of using polyurethane hot melt adhesive to seal the edge, and the nanocomposite loaded with rare earth elements cannot be exposed.
[0023] Furthermore, in step (3), the formation conditions of the prepolymer are: mixing melamine and formaldehyde, adjusting the pH to 8-9 with triethanolamine, heating to 75-80°C and reacting for 0.3-0.5h; the formation conditions of the emulsion are: adding emulsifier and distilled water to the nanocomposite loaded with rare earth elements, stirring at a speed of 1500-2000r / min for 10-15min; the mass ratio of the nanocomposite loaded with rare earth elements, emulsifier and distilled water is 1: (0.3-0.5): (10-15); the emulsifier is Tween-80.
[0024] Furthermore, in step (2), the preparation method of the modified nano-mineral crystal is: ultrasonically mix the nano-mineral crystal and the silane coupling agent for 5 minutes, react at 70-90°C for 1-2 hours, centrifuge at a speed of 10000-12000 r / min for 3-5 minutes, and vacuum dry for 2-4 hours to obtain the modified nano-mineral crystal.
[0025] Polyurethane hot melt adhesive will release some volatile harmful gases, which are harmful to the human body. Nano-mineral crystals have a large specific surface area and abundant adsorption active sites, and can efficiently adsorb various pollutants and harmful gases. However, nano-mineral crystals are inorganic materials. Modification of them can increase their compatibility with the hot melt adhesive system.
[0026] Furthermore, the silane coupling agent is silane coupling agent KH-550; the added amount of the silane coupling agent is 1-5% of the mass of the nano mineral crystal.
[0027] Furthermore, in step (2), the preparation method of the modified mineral wool is: breaking the mineral wool into fiber filaments with a length of 5-50 mm, and subjecting the fiber filaments to plasma treatment with a fluorine-containing gas.
[0028] Mineral wool has good thermal insulation properties and can prevent the adhesive layer from expanding and contracting in an environment with large temperature changes, resulting in problems such as edge warping. However, mineral wool easily absorbs moisture, which affects the thermal insulation effect. Therefore, the mineral wool is subjected to plasma hydrophobic treatment, and fluorine-containing functional groups are bonded and grafted onto the free radicals. The surface of the material is fluorinated to achieve a hydrophobic effect, thereby greatly improving the hydrophobic properties of the material surface.
[0029] Furthermore, the conditions for the plasma treatment are: equipment power is 800-1000W, and the treatment speed is 15mm / s.
[0030] Furthermore, in step (2), the tackifying resin is a mixture of rosin resin and terpene resin in a mass ratio of (1.3-1.8): (1.5-2.5).
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The polyurethane hot melt adhesive prepared by the method of the present invention has a fast curing speed, good bonding performance, high aging resistance, and less release of harmful gases during use.
[0032] (2) The present invention prepares polypropylene carbonate from carbon dioxide generated by the reaction of isocyanate and plant-based polyols, thereby reducing the generation of waste and reducing the emission of greenhouse gases. In addition, the polypropylene carbonate polyol can react with isocyanate to synthesize a polyurethane hot melt adhesive having excellent chemical resistance and good low-temperature resistance. When the polyurethane hot melt adhesive is mixed with the polyurethane hot melt adhesive synthesized using plant-based polyols, the obtained polyurethane hot melt adhesive has excellent properties and outstanding bonding properties to wood.
[0033] (3) The present invention accelerates the curing of the internal polyurethane hot melt adhesive by adding nanocomposite microcapsules, thereby effectively improving the anti-aging performance of the polyurethane hot melt adhesive. Among them, the negative ion mud can release a large amount of negative oxygen ions to decompose harmful substances such as formaldehyde; diatomaceous earth can adsorb impurities on the surface of the board and effectively remove the odor of isocyanate and wood; aluminum oxide can improve the water resistance and thermal insulation performance of the hot melt adhesive and improve the anti-aging performance of the hot melt adhesive; rare earth elements can improve the anti-ultraviolet performance of the hot melt adhesive and delay the aging process of the hot melt adhesive.
[0034] (4) The present invention can efficiently adsorb various pollutants and harmful gases by adding nano-mineral crystals, and modify them to increase their compatibility with the hot melt adhesive system.
[0035] (5) The present invention adds modified mineral wool, which has good thermal insulation performance and prevents the adhesive layer from expanding and contracting in an environment with large temperature changes, thereby preventing the edge of the seal from warping. DETAILED DESCRIPTION
[0036] Example 1 A method for preparing a polyurethane hot melt adhesive for wood edge banding comprises the following steps: (1) 40 parts of diphenylmethane diisocyanate and 50 parts of polyol were mixed, 1.0 part of dimorpholine diethyl ether was added, and the mixture was stirred at 70° C. for 30 minutes; the polyol was a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of 2:1; (2) Add 10 parts of polypropylene carbonate, 15 parts of nanocomposite microcapsules, 5 parts of modified nano mineral crystals, 5 parts of modified mineral wool, and 15 parts of a tackifier to the solution of step (1), and mix at 130° C. for 2 hours to obtain a polyurethane hot melt adhesive; the tackifier resin is a mixture of rosin resin and terpene resin in a mass ratio of 1.3:2.5.
[0037] Example 2 A method for preparing a polyurethane hot melt adhesive for wood edge banding comprises the following steps: (1) 60 parts of triphenylmethane triisocyanate and 70 parts of polyol were mixed, 2.0 parts of N,N-dimethylcyclohexylamine were added, and the mixture was stirred at 85° C. for 20 minutes; the polyol was a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of 3:1; (2) Add 15 parts of polypropylene carbonate, 10 parts of nanocomposite microcapsules, 3 parts of modified nano mineral crystals, 8 parts of modified mineral wool, and 20 parts of a tackifier to the solution of step (1), and mix at 100° C. for 3 hours to obtain a polyurethane hot melt adhesive; the tackifier resin is a mixture of rosin resin and terpene resin in a mass ratio of 1.8:1.5.
[0038] Example 3 A method for preparing a polyurethane hot melt adhesive for wood edge banding comprises the following steps: (1) 50 parts of toluene diisocyanate and 60 parts of polyol were mixed, 1.0 part of triethylamine was added, and the mixture was stirred at 80° C. for 25 minutes; the polyol was a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of 2.5:1; (2) Add 10 parts of polypropylene carbonate, 12 parts of nanocomposite microcapsules, 4 parts of modified nano mineral crystals, 6 parts of modified mineral wool, and 15 parts of a tackifier to the solution of step (1), and mix at 115° C. for 2.5 hours to obtain a polyurethane hot melt adhesive; the tackifier resin is a mixture of rosin resin and terpene resin in a mass ratio of 1.5:2.0.
[0039] Example 4 A method for preparing a polyurethane hot melt adhesive for wood edge banding comprises the following steps: (1) Mix 50 parts of toluene diisocyanate and 50 parts of polyol, add 1.5 parts of dimethylethanolamine, and stir at 80°C for 25 minutes; the polyol is a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of 2.5:1; (2) Add 15 parts of polypropylene carbonate, 12 parts of nanocomposite microcapsules, 4 parts of modified nano mineral crystals, 6 parts of modified mineral wool, and 15 parts of a tackifier to the solution of step (1), and mix at 115° C. for 2.5 hours to obtain a polyurethane hot melt adhesive; the tackifier resin is a mixture of rosin resin and terpene resin in a mass ratio of 1.5:2.0.
[0040] Comparative Example 1 In step (2), no polypropylene carbonate is added, and the remaining steps are the same as those in Example 3.
[0041] Comparative Example 2 In step (2), no nanocomposite microcapsules are added, and the remaining steps are the same as those in Example 3.
[0042] Comparative Example 3 In step (2), no modified nano-mineral crystals are added, and the remaining steps are the same as those in Example 3.
[0043] Comparative Example 4 In step (2), modified mineral wool is not added, and the other steps are the same as those in Example 3.
[0044] Comparative Example 5 The modified nano-mineral crystals in step (2) are replaced with nano-mineral crystals, and the remaining steps are the same as those in Example 3.
[0045] Comparative Example 6 The modified mineral wool in step (2) is replaced with mineral wool, and the remaining steps are the same as those in Example 3.
[0046] Comparative Example 7 In step (2), no negative ion mud is added to the nanocomposite microcapsules, and the remaining steps are the same as those in Example 3.
[0047] Experimental Example 1 The various properties of the polyurethane hot melt adhesives of Examples 1-4 were tested, and the test results are listed in Table 1.
[0048] Table 1. Properties of polyurethane hot melt adhesive As can be seen from Table 1, the polyurethane hot melt adhesives of Examples 1-4 have excellent bonding properties and aging resistance, short surface drying time, fast curing speed, fast internal curing speed, short time required for complete curing, and the amount of formaldehyde released is measured, which is small and meets national regulations.
[0049] Experimental Example 2 The various properties of the polyurethane hot melt adhesives of Example 3 and Comparative Examples 1-4 were tested, and the test results are listed in Table 2.
[0050] Table 2. Properties of polyurethane hot melt adhesive As can be seen from Table 2, in Comparative Example 1, no polypropylene carbonate was added, and the bonding performance of the polyurethane hot melt adhesive was reduced; in Comparative Example 2, no nanocomposite microcapsules were added, and the aging resistance of the polyurethane hot melt adhesive was reduced, and the formaldehyde release increased; in Comparative Example 3, no modified nano-mineral crystals were added, and the formaldehyde release of the polyurethane hot melt adhesive increased; in Comparative Example 4, no modified mineral wool was added, and when the external temperature changed, the bonding performance of the polyurethane hot melt adhesive decreased. The polyurethane hot melt adhesive prepared by the method of the present invention has excellent bonding performance and aging resistance, and can also maintain the original excellent performance when the external temperature changes greatly.
[0051] Experimental Example 3 The various properties of the polyurethane hot melt adhesives of Example 3, Comparative Example 3 and Comparative Example 5 were tested, and the test results are listed in Table 3.
[0052] Table 3. Properties of polyurethane hot melt adhesive As can be seen from Table 3, the addition of nano-mineral crystals in Comparative Example 5 can reduce the release of formaldehyde, but since the nano-mineral crystals are inorganic materials, they have poor compatibility with the polyurethane hot melt adhesive system, which will affect the bonding properties of the polyurethane hot melt adhesive. The modified nano-mineral crystals added in the present invention can efficiently adsorb various pollutants and harmful gases, and have good compatibility with the hot melt adhesive system, and the polyurethane hot melt adhesive has good bonding properties.
[0053] Experimental Example 4 The various properties of the polyurethane hot melt adhesives of Example 3, Comparative Example 4 and Comparative Example 6 were tested, and the test results are listed in Table 4.
[0054] Table 4. Properties of polyurethane hot melt adhesive As can be seen from Table 4, compared with Comparative Example 4, the addition of mineral wool in Comparative Example 6 can improve the bonding performance of the polyurethane hot melt adhesive, and the bonding performance of the polyurethane adhesive changes relatively little under temperature changes, because mineral wool has good thermal insulation performance and prevents the adhesive layer from expanding and contracting significantly, but mineral wool easily absorbs moisture and affects the thermal insulation effect. Therefore, the present invention adds modified mineral wool to enable the polyurethane hot melt adhesive to have good bonding performance even when the temperature changes significantly.
[0055] Experimental Example 5 The various properties of the polyurethane hot melt adhesives of Example 3, Comparative Example 2 and Comparative Example 7 were tested, and the test results are listed in Table 5.
[0056] Table 5. Properties of polyurethane hot melt adhesive It can be seen from Table 5 that compared with Example 3, Comparative Example 7 did not add negative ion mud, the curing rate of the polyurethane hot melt adhesive was reduced, and the formaldehyde release amount was increased. This is because the negative ion mud has a strong moisture absorption and release function, which can absorb moisture when the humidity is high and release moisture when the humidity is low, effectively adjusting the dryness and wetness, ensuring the rapid curing of the polyurethane hot melt adhesive, and can release a large amount of negative oxygen ions, which can decompose harmful substances such as formaldehyde.
[0057] In summary, the present invention can effectively improve the curing speed of the polyurethane hot melt adhesive, enhance the bonding performance of the polyurethane hot melt adhesive, reduce the emission of harmful gases, and ensure that the polyurethane hot melt adhesive still has excellent bonding performance under temperature changes by adding polypropylene carbonate, nanocomposite microcapsules, modified nano mineral crystals, and modified mineral wool.
[0058] The testing method in the specific implementation mode is as follows: (1) The bonding performance of polyurethane hot melt adhesive was tested according to GB / T7124-2008 standard. The deep curing rate was measured by injecting adhesive into a wedge-shaped groove made of a non-stick material to the hot melt adhesive from the lowest point of the groove to fill the groove evenly and without voids. Use a scraper to remove excess adhesive from the groove surface to ensure that the adhesive surface is flat and free of defects. Place in a constant temperature room at 25°C and 55% RH. After 24 hours, start from the highest point of the groove and lift up the sealant until the uncured adhesive is seen attached to the wedge-shaped groove. Measure the thickness of the cured adhesive strip and use this thickness to characterize the deep curing rate.
[0059] (2) According to the formaldehyde emission determination in GB / T 17657-2022, the formaldehyde emission of polyurethane hot melt adhesive was tested using the 1 cubic climate chamber method.
Claims
1. A method for preparing a polyurethane hot melt adhesive for wood edge banding, characterized in that: The following steps are involved: (1) Mix isocyanate and polyol, add catalyst, and react at 70-85°C for 20-30 minutes; (2) Add polypropylene carbonate, nanocomposite microcapsules, modified nano mineral crystals, modified mineral wool, and a tackifier to the solution of step (1), and mix at 100-130° C. for 2-3 hours to obtain a polyurethane hot melt adhesive.
2. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: The components of the polyurethane hot melt adhesive are as follows: by weight, 40-60 parts of isocyanate, 50-70 parts of polyol, 0.5-2.0 parts of catalyst, 10-15 parts of polypropylene carbonate, 10-15 parts of nanocomposite microcapsules, 3-5 parts of modified nano mineral crystals, 5-8 parts of modified mineral wool, and 10-20 parts of tackifier.
3. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: In step (1), the polyol is a mixture of plant-based polyol and vegetable oil-based polyol in a mass ratio of (2-3):
1.
4. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: In step (2), the preparation method of polypropylene carbonate is: reacting carbon dioxide, propylene oxide and a catalyst at 80-120° C. for 3-5 hours to obtain polypropylene carbonate.
5. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 4, characterized in that: The mass ratio of propylene oxide to catalyst is 1:(0.05-0.07).
6. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: In step (2), the preparation method of the nanocomposite microcapsules is: (1) Adding negative ion mud, bentonite and nano-alumina to polyethylene glycol and hydrochloric acid solution, ultrasonicating for 30-40 minutes, then adding ammonia solution, heating to 90-110°C for reaction for 2-3 hours, filtering, drying and calcining for 3-5 hours to obtain a nano-alumina / negative ion mud-bentonite composite; (2) immersing the nano-alumina / negative ion mud-bentonite composite in a rare earth element salt solution, ultrasonicating for 20-30 minutes, filtering, washing, and drying at 100-120° C. to obtain a nano-composite loaded with rare earth elements; (3) Melamine and formaldehyde are reacted under alkaline conditions to form a prepolymer, and then the nanocomposite loaded with rare earth elements is emulsified at 25-30°C to form an emulsion. Finally, the prepolymer is adjusted to a pH of 5.0-5.5 with an acrylic acid solution, mixed with the emulsion for 15-20 minutes, filtered, and dried to obtain nanocomposite microcapsules.
7. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 6, characterized in that: In step (1), the mass ratio of the negative ion mud, bentonite and nano-alumina is (1-1.5):1:(1.5-2.5).
8. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: In step (2), the preparation method of the modified nano-mineral crystal is: ultrasonically mix the nano-mineral crystal and the silane coupling agent for 5 minutes, react at 70-90° C. for 1-2 hours, centrifuge at a speed of 10000-12000 r / min for 3-5 minutes, and vacuum dry for 2-4 hours to obtain the modified nano-mineral crystal.
9. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 8, characterized in that: The silane coupling agent is silane coupling agent KH-550; the added amount of the silane coupling agent is 1-5% of the mass of the nano mineral crystal.
10. The method for preparing polyurethane hot melt adhesive for wood edge banding according to claim 1, characterized in that: In step (2), the preparation method of the modified mineral wool is: breaking the mineral wool into pieces to form fiber filaments with a length of 5-50 mm, and subjecting the fiber filaments to plasma treatment with a fluorine-containing gas.